Enhanced Specific Heat of Chloride Salt with Mg Particles for High-temperature Thermal Energy Storage. (May 2017) - Tian, Heqing; Du, Lichan; Huang, Chenglong; Wei, Xiaolan; Wang, Weilong; Ding, Jing
Abstract: The specific heat of molten salts plays a key role to reduce the costs of thermal storage for concentrating solar power plants. In this study, two different mass concentrations Mg particles were dispersed in a binary chloride molten salt to improve its specific heat used as a high temperature heat storage and transportation medium. The influence of Mg particle morphologies and mass concentrations on the specific heat of nanosalts were investigated. Results showed that Mg particles dissolved as elemental metal and dispersed as stone-like blocky in molten salt. The melting temperature of the molten salt had almost no change. The average value of specific heat was obviously improved up to 3% (1.0 wt% Mg) and 7% (2.0 wt% Mg) in solid phase, respectively.